Correlation between Myocardial Fibrosis Patterns and Sudden Cardiac Death in Young Adults: A Clinico-Anatomical and Forensic Study - Rajesh, Rajesh; Khilji, Abdullah; Rukhsar, Hina; Shaikh, Muhammad Rafique (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The sudden cardiac death (SCD) in young adults is most likely to be without any previous symptoms, and underlying abnormalities in the myocardium can be difficult to detect in life. Myocardial fibrosis, especially with its existence in subtle or hidden patterns has become a possible structural marker which can predetermine lethal arrhythmias. Objective: To examine the relationship between myocardial fibrosis patterns and SCD in young adults by integrating cardiac imaging, histopathology, and forensic autopsy findings. Methodology: This retrospective study involved 72 consecutive cases of young adults (18 40 years old) who had suffered sudden cardiac death during the period between January 2021 and January 2022 in Khairpur Medical College, Khairpur Mir’s. Review of cardiac MRI, histological sections, and autopsy examinations were done to evaluate the burden of fibrosis, anatomical distribution, late gadolinium enhancement (LGE) patterns and conduction system involvement. Predictors of SCD were determined by statistical comparisons and regression analysis. Results: Mid-myocardial and patchy LGE images, replacement fibrosis and septal scarring had a strong correlation with high fibrosis burden (p < 0.001). Such individuals were also found to have increased heart weight, thickening of ventricle walls and increased involvement of the conduction system. Septal scar, replacement fibrosis and mid-myocardial LGE became independent predictors of SCD. Conclusion: Among young adults, myocardial fibrosis is a major structural substrate of sudden cardiac death. The strong agreement of the imaging, microscopic and autopsy data points to the role of early detection of silent myocardial injury and the position of advanced imaging technology as the means of risk stratification.